Calidad de vida de pacientes diabéticos tipo 2 atendidos en el Hospital iii de Essalud Iquitos-2022 - Aspajo Yume, Daniel (2023)
Problem: ¿What is the quality of life of type 2 diabetic patients treated at Hospital III of Essalud Iquitos - 2022? Objective: To determine the quality of life of type 2 diabetic patients treated at Hospital III of Essalud Iquitos – 2022. Materials and methods: The research is descriptive, observational, prospective and non-experimental cross-sectional design, which included a population of 154 type 2 diabetic patients, with a sample of 110 patients. Results: In the epidemiological characteristics it was possible to observe that 53.6% were female patients and 46.4% male patients, the level of quality of life was low in 54.5% of the patients and high in 45.5% of the patients, regarding the physical function scale it was low in 53.6% of the patients and high in 46.4% of the patients, in the bodily pain scale it was low in 68.2 % of patients and high 31.8% of patients, on the general health scale it was low in 51.8% of patients and high in 48.2% of patients, on the vitality scale it was low in 57 3% of the patients and high in 42.7% of the patients, in the mental health component it was low in 70% of the patients and high in 30% of the patients. There is evidence of a significant statistical relationship between quality of life and age, marital status, smoking and hypertension. No relationship was found with sex, educational level and place of origin.